The Irish Meet the Welsh Wizard: Character, Narrative, and Political Rationality in the Formation of the Irish Free State. Issue 3 (2nd July 2016) - Meadwell, Hudson
Abstract : The negotiations that led to the formation of the Irish Free State in 1921 form the focus of this article. A longstanding interpretation of these negotiations has the British finessing the Irish by playing on the weaknesses of character of the Irish delegation. This interpretation is both flawed and influential. On one level, the article questions its historical accuracy and proposes an alternative. On another level, the article seeks to account for its enduring importance. This interpretation plays a role in a larger narrative of Anglo-Irish relations that is rooted in British colonialism and Irish nationalism.